1990
DOI: 10.1021/bi00499a006
|View full text |Cite
|
Sign up to set email alerts
|

Participation of hydrogen ion in the calcium-induced conformational transition of 4-nitro-2,1,3-benzoxadiazole-labeled sarcoplasmic reticulum ATPase

Abstract: The binding of Ca2+ to 4-nitro-2,1,3-benzoxadiazole (NBD)-labeled sarcoplasmic reticulum Ca2(+)-ATPase was accelerated markedly when the pH was changed at 11 degrees C from 6.5 to 8.0 at the time of Ca2+ addition. We examined the effect of pH on the enzyme conformational transition by measuring the kinetics of NBD fluorescence rises induced by a pH jump under various ligand conditions. The fast fluorescence rise following a pH jump from 6.0 or 6.5 to various test pHs in the presence and absence of Ca2+ proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…However, from a kinetic point of view the rate of the E2 to Ca 2 E1 transition is generally thought to be rate-limited not by Ca 2ϩ binding per se but by a conformational transition occurring either after binding of the first Ca 2ϩ ion (78), or, alternatively before binding of Ca 2ϩ , an event accompanied by deocclusion of intramembraneous protons bound to the translocation sites in the E2 state (80,81). Thus, the slowing down of the E2 to Ca 2 E1 transition in ADA ATPase seems to favor an indirect effect of the mutation, as further discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…However, from a kinetic point of view the rate of the E2 to Ca 2 E1 transition is generally thought to be rate-limited not by Ca 2ϩ binding per se but by a conformational transition occurring either after binding of the first Ca 2ϩ ion (78), or, alternatively before binding of Ca 2ϩ , an event accompanied by deocclusion of intramembraneous protons bound to the translocation sites in the E2 state (80,81). Thus, the slowing down of the E2 to Ca 2 E1 transition in ADA ATPase seems to favor an indirect effect of the mutation, as further discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…7). Because other partial reaction steps that contribute to rate limitation of the overall reaction, such as the E 1 ϳP(Ca 2 ) to E 2 P and E 2 to E 1 Ca 2 transitions, tend to be accelerated at alkaline pH (49,52,59), and the dephosphorylation of E 2 P remained relatively fast in the SERCA3 enzymes under these conditions, a higher turnover rate could be reached at alkaline pH in the SERCA3 enzymes as compared with SERCA1a. Furthermore, because the rate of E 2 P dephosphorylation was higher in SERCA3b than in the other SERCA3 enzymes at alkaline pH, SERCA3b reached the highest turnover rate at pH optimum (Figs.…”
Section: Fig 13 Vanadate Inhibition During Steady-state Atp Hydrolymentioning
confidence: 99%
“…It has been shown that Ca 2+ binding occurs in exchange with H + [13,14], and the stoichiometry of exchange is dependent on medium pH [15]. Ca 2+ /H + exchange is of interest both for the involvement of carboxylic amino acid chains in Ca 2+ binding at the start of the ATPase cycle, and for the subsequent release of bound Ca 2+ following ATP utilization and enzyme turnover [16,17].…”
mentioning
confidence: 99%